A simple template-free bioinspired route of 1D Bi2S3 nanorods synthesis for electrochemical CO2 reduction to formate - Chowdhury, Anirban; Bhan, Chandra; Rao Peela, Nageswara; Kumar Golder, Animes (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
[Display omitted] •Development of a bioinspired process of template-free synthesis of 1D Bi2S3 nanorods.•Mechanistic exploitation of Bi2S3 nanorods formation mediated by plant-based analyte.•Bi2S3 nanorods electrocatalyzed CO2 conversion to HCOO– with high Faradaic efficiency.•Oxidation of Bi2S3-NRs(bio) to Bi2O2CO3, could serve as active sites during ECO2RR. This work demonstrates a simple bioinspired route of synthesizing template-free 1D Bi2S3 nanorods, Bi2S3-NRs(bio), using Sechium edule fruit. The morphology of nanorods was controlled via capping of ascorbic acid (AA), a major bio-analyte. The average length and diameter were reduced from 485 to 229.5 nm and 123 to 31 nm, respectively, compared with Bi2S3-NRs(control), Bi2S3 nanorods synthesized in the absence of bio-extract/reducing agent. The XPS analysis confirmed that the formation of Bi2O3 in Bi2S3-NRs(control), could be prevented in Bi2S3-NRs(bio) because of AA capping. A plausible mechanistic route of synthesis of Bi2S3-NRs(bio) is also proposed herein. The modified Bi2S3-NRs(bio)/Toray carbon paper (TCP) electrode exhibited selective HCOO– formation with FE of 92.3% against 50.9% for the Bi2S3-NRs(control)/TCP electrode at −1.5 V (vs. Ag/AgCl). Higher FE exhibited by Bi2S3-NRs(bio) catalyst has resulted from its compositional and morphological attributes. In-situ electrochemical oxidation of Bi2S3-NRs(bio) to Bi2O2CO3 also could act as active sites for enhanced and selective HCOO– formation.